2021
DOI: 10.1097/meg.0000000000002013
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospitalization proton pump inhibitor use and clinical outcomes in COVID-19

Abstract: Introduction Severe acute respiratory syndrome coronavirus-2 may escape the inactivation by gastric acid because of hypochlorhydria caused by proton pump inhibitors (PPIs), which could predispose the patients to severe COVID-19. Methods We studied the association between prehospitalization PPI exposure and clinical outcomes among hospitalized COVID-19 patients. Results A total of 295 hospitalized COVID-19 patients were included in the study. 15.6% of hospitalized COVID-19 patients were on PPIs at home. Mortali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 33 publications
(40 reference statements)
0
32
0
1
Order By: Relevance
“…Only 4 studies 12,19,20 reported the association between current PPI use and mortality alone, including 4150 current PPI users (Supplementary Table 7). The overall analysis showed an RR of 1.33 (95% CI, 0.71-2.48) in current PPI users compared with never users, although estimates differed between studies with low risk of bias, RR 0.85 (95% CI, 0.70-1.03), and high risk of bias, RR 2.37 (1.53-3.67) (interaction test: P < .0001) (Figure 2).…”
Section: Meta-analysis Of Coronavirus Disease 2019 Mortalitymentioning
confidence: 99%
“…Only 4 studies 12,19,20 reported the association between current PPI use and mortality alone, including 4150 current PPI users (Supplementary Table 7). The overall analysis showed an RR of 1.33 (95% CI, 0.71-2.48) in current PPI users compared with never users, although estimates differed between studies with low risk of bias, RR 0.85 (95% CI, 0.70-1.03), and high risk of bias, RR 2.37 (1.53-3.67) (interaction test: P < .0001) (Figure 2).…”
Section: Meta-analysis Of Coronavirus Disease 2019 Mortalitymentioning
confidence: 99%
“…Taking into account the study by Hariyanto et al [ 53 ], we included data on the severity of the disease, specifically for 16 patients and 77 patients with shock, respectively, in the PPI-group and in the non-PPI-group[ 50 ], 18 patients and 30 patients had secondary infection, respectively, in the PPI-group and in the non-PPI-group[ 31 ]. A study by García-Menaya et al [ 55 ] included data related to severity and mortality of the disease, but they were calculated for patients with and without allergic conditions and for overall patients.…”
Section: Resultsmentioning
confidence: 99%
“…Almario showed that PPI use is associated with a higher likelihood of testing positive for SARS-CoV-2 infection 5 . The basis for these findings is presently purely speculative and is explored in detail in the aforementioned publications [5][6][7] . Importantly, PPIs represent a medication that could be safely suspended during acute COVID-19 illness given their indication is commonly for symptomatic relief.…”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%
“…A limited number of studies have examined certain classes of medication in the context of SARS-CoV-2 infection, revealing several robust associations [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Some point to the clear opportunity for adjusting prescriptions to the benefit of patients admitted with COVID-19 with greater understanding of how the disease interacts with commonly used agents 6 .…”
Section: Introductionmentioning
confidence: 99%